Exome sequencing in single cells from the cerebrospinal fluid in multiple sclerosis. (October 2014) - Kemppinen, AK; Baker, A; Liao, W; Fiddes, B; Jones, J; Compston, A; Ban, M; Sawcer, S
Background: Genome-wide association studies (GWAS) have identified over 100 germline variants that influence susceptibility to multiple sclerosis, most of which map within or near to genes with immunological function. However, the role of somatic mutations in multiple sclerosis has not been investigated. Objective: The objective of this paper is to explore the role that somatic mutations might play in the development of multiple sclerosis. Methods: We exome-sequenced in total 21 individual CD4+ lymphocytes isolated from cerebrospinal fluid of two patients. In addition we sequenced DNA from the patients' peripheral blood to serve as germline reference. Results: In comparison with the respective germline sequence, each cell differed at an average of 1784 positions, but as anticipated subsequent analysis confirms that most, if not all, of these potential mutations are likely to represent artefacts generated during the amplification of a single genome and/or by sequencing. Fifty-six of the potential mutations were predicted to have likely functional effects on genes that have previously been implicated by GWAS, including three in the CD6 gene. Conclusion: More robust methods applied to larger numbers of cells will be needed to define the role of somatic mutations.